2018
DOI: 10.1021/acs.jpcc.8b04718
|View full text |Cite
|
Sign up to set email alerts
|

Direct Evidence of Surface Charges in n-Type Al-Doped ZnO

Abstract: The fundamental properties of electrons in the prototypical n-type oxide nanocrystal, Al 3+ -doped ZnO, have been studied at both the ensemble and single-particle levels by spectroscopic and electron force microscopic techniques. We developed and implemented a new synthetic methodology that enables the tunable incorporation of Al 3+ in the ZnO nanocrystal in an "etching−regrowth−doping" (ERD) strategy in a single-pot reaction. The ensemble-averaged properties and evolution of the Al 3+ speciation in ZnO were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 36 publications
3
27
0
Order By: Relevance
“…It is worth noting that similar effects have been observed previously for various metal oxide NCs, including ZnO. 41,42,43,44 As mentioned earlier, all synthesized particles are crystalline, as confirmed by XRD data as well as by high resolution TEM and the associate Fast Fourier Transform (FFT) presented in Figure 2f,g. Importantly, while we studied the growth of ZnO by isolating the nucleation event through the swift injection of the first 0.33 mmol of precursor, we demonstrated that this modification has little or no effect on the final product compared to a conventional continuous addition method, as shown in Figure S2 and Figure S4.…”
Section: Resultssupporting
confidence: 85%
“…It is worth noting that similar effects have been observed previously for various metal oxide NCs, including ZnO. 41,42,43,44 As mentioned earlier, all synthesized particles are crystalline, as confirmed by XRD data as well as by high resolution TEM and the associate Fast Fourier Transform (FFT) presented in Figure 2f,g. Importantly, while we studied the growth of ZnO by isolating the nucleation event through the swift injection of the first 0.33 mmol of precursor, we demonstrated that this modification has little or no effect on the final product compared to a conventional continuous addition method, as shown in Figure S2 and Figure S4.…”
Section: Resultssupporting
confidence: 85%
“…Main‐group metal elements, such as Na, [33] Al, [3] Ga, [34] In [35] and Sn [16] element etc, were widely used as dopants of ZnO. According to the various doping elements, it can divide into p‐type and n‐type doping [33,36a,b,c] . When the dopant is the GroupI (Li, Na and K), the p‐type doping characteristic appears.…”
Section: Metal Element Dopingmentioning
confidence: 99%
“…The self‐compensation response of acceptor doping is inhibited and the acceptor energy level generated, which induces the material p‐type conductive characteristics. The n‐type doping (donor doping) behavior appears with metals (Al, Ga, In, Sn) as the ZnO dopants [36a] . The donor doping can produce a large number of donor electrons, which improves the conductivity of ZnO, induces the defects and reduces grain size of ZnO.…”
Section: Metal Element Dopingmentioning
confidence: 99%
“…[1][2][3][4][5][6] Since the 1980s, the significant role of dimensionality has been recognized apart from the bulk phase, inspiring the swift development of low-dimensional materials (0D, 1D, 2D). [7][8][9][10] The realm of 0D quantum dots, [11][12][13][14] 1D nanowire, [15][16][17][18][19] nanotube, [20][21][22][23][24] etc., has become hot research spots in succession. However, 2D materials remained to be a silent zone somehow.…”
Section: Introductionmentioning
confidence: 99%